2020
DOI: 10.3389/fmed.2020.577578
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mesenchymal Stem Cell-Derived Exosomal miR-25 Regulates the Ubiquitination and Degradation of Runx2 by SMURF1 to Promote Fracture Healing in Mice

Abstract: Recent evidence has demonstrated that mesenchymal stem cells (MSCs) can release a large number of functionally specific microRNA (miRNA) microvesicles that play a role in promoting osteogenic differentiation, but the specific mechanism is not yet clear. Under such context, this study aims to elucidate the mechanism of bone marrow mesenchymal stem cell-derived exosomes (BMSC-Exo) promoting fracture healing in mice. We isolated and identified the BMSC-Exo. Bioinformatics analysis predicted high expression of miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…On the other hand, MVs are natural membrane vesicles secreted, thus they are proved to have lower immunogenicity and toxicity, and are more efficiently absorbed by target cells than other synthetic delivery vehicles, such as liposomes, micelles, dendrimers and nanocapsules [ 22 ]. It has been proved that MMVs may promote the proliferation of osteoblasts through regulating transcription activity and expression level of genes [ 23 , 24 ]. There were studies to report pericytes-derived microvesicles (PMVs) from human cerebrovascular sources may carry neuroprotective factors, including VEGF, BDNF, and PLGF, to reduce nerve cell damage [ 25 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, MVs are natural membrane vesicles secreted, thus they are proved to have lower immunogenicity and toxicity, and are more efficiently absorbed by target cells than other synthetic delivery vehicles, such as liposomes, micelles, dendrimers and nanocapsules [ 22 ]. It has been proved that MMVs may promote the proliferation of osteoblasts through regulating transcription activity and expression level of genes [ 23 , 24 ]. There were studies to report pericytes-derived microvesicles (PMVs) from human cerebrovascular sources may carry neuroprotective factors, including VEGF, BDNF, and PLGF, to reduce nerve cell damage [ 25 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recipient MSCs, miR-335 inhibited the in vitro expression of the pro-osteoclastogenic protein VAPB, promoting the activation of Wnt/β-catenin pathway, and therefore stimulating the osteogenesis of MSCs, plus, finally the in vivo fracture repair in mice models [35]. BM-MSCs-EVs also have been shown to promote fracture healing in mice mediated by enriched miR-25, which facilitates osteogenic differentiation, proliferation, and migration of osteoblasts by inhibiting RUNX2 degradation through downregulation of the ubiquitin ligase SMURF1 [36].…”
Section: Evs Derived From Bm-mscsmentioning
confidence: 99%
“…Presumably by enhancing Rac1 expression, miR-25 activated PI3K/AKT and c-Jun N-terminal kinase pathways, leading to enhanced osteoblastic viability and migration, as well as increased expression levels of osteogenic marker genes RUNX2 and OCN (80). Research by Jiang et al showed that miR-25 also targeted the expression SMURF1, thereby enhancing RUNX2 signalling and subsequently promoting osteogenic differentiation (81). Hu et al examined the interaction of miR-26b with the Wnt-signalling pathway in rat BMSCs.…”
Section: Osteogenesis and Osteoblastogenesismentioning
confidence: 99%